United Nations Resolution 69/32 on the 'No first placement of weapons in space': A step forward in the prevention of an arms race in outer space?. (November 2016) - Liu, Hao; Tronchetti, Fabio
Abstract: On 2 December 2014, the United Nations General Assembly (UNGA) adopted with a vote of 126 in favor, 4 against and 46 abstentions, Resolution 69/32 entitled 'No first placement of weapons in space. Despite the limited attention received in academic circles, the adoption of Resolution 69/32 represents an important development in the area of space security. First, it indicates the growing recognition of the positive role that transparency and confidence-building measures (TCBMs) play in preventing an arms race in space (PAROS), even from the perspective of those States that has suggested the adoption of a treaty on PAROS, namely China and Russia. Second, it shows the willingness of a crescent number of members of the United Nations General Assembly to engage in initiatives aimed at promoting a more secure space environment. Third, its controversial reception proves that a universal solution to the issue of space security still lays far ahead. In the light of these elements the purpose of the present viewpoint is to analyze Resolution 69/32, evaluate its positive and negative features, and assess its chances to provide a meaningful contribution to a more secure outer space.